Optical biosensing of monkeypox virus using novel recombinant silica-binding proteins for site-directed antibody immobilization - Xixi Song; Ying Tao; Sumin Bian; Mohamad Sawan (Elsevier, 2024)
The efficient immobilization of capture antibodies is crucial for timely pathogen detection during global pandemic outbreaks. Therefore, we proposed a silica-binding protein featuring core functional domains (cSP). It comprises a peptide with a silica-binding tag designed to adhere to silica surfaces and tandem protein G fragments (2C2) for effective antibody capture. This innovation facilitates precise site-directed immobilization of antibodies onto silica surfaces. We applied cSP to silica-coated optical fibers, creating a fiber-optic biolayer interferometer (FO-BLI) biosensor capable of monitoring the monkeypox virus (MPXV) protein A29L in spiked clinical samples to rapidly detect the MPXV. The cSP-based FO-BLI biosensor for MPXV demonstrated a limit of detection (LOD) of 0.62 ng/mL in buffer, comparable to the 0.52 ng/mL LOD achieved using a conventional streptavidin (SA)-based FO-BLI biosensor. Furthermore, it achieved LODs of 0.77 ng/mL in spiked serum and 0.80 ng/mL in spiked saliva, exhibiting no cross-reactivity with other viral antigens. The MPXV detection process was completed within 14 min. We further proposed a cSP-based multi-virus biosensor strategy capable of detecting various pandemic strains, such as MPXV, the latest coronavirus disease (COVID) variants, and influenza A protein, to extend its versatility. The proposed cSP-modified FO-BLI biosensor has a high potential for rapidly and accurately detecting MPXV antigens, making valuable contributions to epidemiological studies.